PENGARUH CSR DAN ENVIRONMENTAL PERFORMANCE TERHADAP NILAI PERUSAHAAN DENGAN GCG VARIABEL MODERATING - Retno, Diajeng; Wahidahwati, Wahidahwati (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis research is aimed to examine empirical evidences about some factors which give influence to the firm value on manufacturing companies which are listed in PROPER of Ministry of Environment and Indonesia Stock Exchange in 2011-2015 periods. Some factors which have been applied in this research are Corporate Social Responsibility, Environmental Performance, Good Corporate Governance as the moderating variable and Size as control variable. The samples are 74 manufacturing companies in 2011-2015 periods which are listed in PROPER of Ministry of Environment and Indonesia Stock Exchange. The sample collection technique has been carried out by using purposive sampling methods. The analysis method has been done by using multiple linear regressions analysis on 5% significance level and statistics test instrument the SPSS 23rd version. The result of the research shows that corporate social responsibilty does not give any influence to the firm value. Environmental performance does not give any influence to the firm value. Good Corporate Governance is unable to moderate Corporate Social Responsibility to the firm value. Good Corporate Governance is able to moderate Environmental Performance to the firm value. Size as the control variable does not give any influence to the firm value.Keywords: Firm value, corporate social responsibility, environmental performance, good corporate governance as the moderating variable, size.